ENCOURAGING INTELLECTUAL AND SPIRITUAL PROGRESS THROUGH THE ISLAMIZATION OF KNOWLEDGE - Dewi Suriyani Djamdjuri; Risa Dwi Almanda (PT. Intelek Cendikiawan Nusantara, 2025)
The Islamization of knowledge (IoK) is the process of merging Islamic beliefs with modern academic subjects to produce knowledge that is both ethical and scientific. It seeks to match education with Islamic beliefs, demonstrating how all knowledge leads to a deeper comprehension of Allah's creation. Despite problems such as misunderstandings within the Muslim community and opposition from secular education systems, IoK can be adopted by modifying curricula, training instructors, and fostering research that combines modern and Islamic knowledge. Using the literature review approach, the conclusion is that transforming education is critical to the Islamization of knowledge. By empowering instructors, introducing Islamic beliefs into courses, and encouraging original research, educational institutions may generate a generation that is both morally and intellectually competent. To ensure that education becomes a tool for addressing contemporary concerns while upholding Islamic ideals, this reform is required to align the pursuit of knowledge with ethical and spiritual accountability while also addressing global issues such as poverty and social justice, ensuring that knowledge serves humanity and promotes fairness, sustainability, and compassion. Finally, IoK provides a solution to today's challenges while encouraging intellectual and spiritual progress.